1980
DOI: 10.1111/j.1439-0485.1980.tb00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Hydrographic and Biological Features of the Gulf of Naples

Abstract: Abstract. Recent observations of physico‐chemical and biological parameters in the Gulf of Naples are summarized. The water masses present within the Gulf during the various periods of the year are described. The temporal and spatial distribution of surface nutrients (N‐NO3, P‐PO4, Si‐SiO4) and chlorophyll a are reported and the areas exposed to local eutrophication are identified. Biweekly sampling at a reference station has permitted us also to identify both phytoplankton and zooplankton seasonal cycles. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 5 publications
4
27
0
Order By: Relevance
“…In the southeastern part of the Gulf of Thermaikos zooplankton abundance was generally low and resembled that observed just outside of the Gulf of Fos (Benon et al 1977), in the Gulf of Naples (Carrada et al 1980) and in the outer Gulf of Saronikos, Greece (Moraitou-Apostolopoulou & Ignatiades 1980). Intermediate values were recorded for the central part of the study area.…”
Section: Discussionsupporting
confidence: 61%
“…In the southeastern part of the Gulf of Thermaikos zooplankton abundance was generally low and resembled that observed just outside of the Gulf of Fos (Benon et al 1977), in the Gulf of Naples (Carrada et al 1980) and in the outer Gulf of Saronikos, Greece (Moraitou-Apostolopoulou & Ignatiades 1980). Intermediate values were recorded for the central part of the study area.…”
Section: Discussionsupporting
confidence: 61%
“…The importance of Mediterranean circulation dynamics in the determination of different zooplankton associations was also found in the Gulf of Trieste (Cataletto, 1995) and in the Gulf of Naples (Carrada et al, 1980). Water masses and marine circulation of the whole Mediterranean Sea, and particularly of the Ligurian Basin, underwent major changes over the three years of the study.…”
Section: Discussionmentioning
confidence: 88%
“…Stn MC is influenced both by coastal waters and by the frequent flushing of oligotrophic Tyrrhennian waters, although no stable frontal structure has been observed in the Gulf of Naples between the 2 water masses (Carrada et al 1980. Precipitation mainly occurs in early spring and in late autumn, with an annual mean of 800 mm m -2 yr -1 ; coastal waters expand out to the study site, as indicated by lower salinity values, after periods of rain.…”
Section: Methodsmentioning
confidence: 99%